My heart will not sit down - Rockliff, Mara (Alfred A. Knopf, 2012)
In 1931 Cameroon, young Kedi is upset to learn that children in her American teacher's village of New York are going hungry because of the Great Depression, and she asks her mother, neighbors, and even the headman for money to help. Includes historical notes.